Picturesque Trinidad - Rice, Ben (My University, 2010)
The postcard shows a man sitting near a tree lined pathway, which leads to a little stream.
Colour: Black and white; Style: Portrait; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Rivers--Trinidad and Tobago; Trees--Trinidad and Tobago; Men--Trinidad and Tobago; [1911]; Trails--Trinidad and Tobago; Bamboo--Trinidad and Tobago